Two new polymorphs of 2,6-diaminopyrimidin-4(3H)-One Monohydrate - Gwaram, N.S.; Olmstead, M.M.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
The title compound, C4H6N4O center dot H2O, crystallized simultaneously as a triclinic and a monoclinic polymorph from an aqueous solution of 2,4-diaminopyrimidin-6-ol. Previously, an orthorhombic polymorph was isolated under the same experimental conditions. The molecular geometric parameters in the two present polymorphs and the previously reported orthorhombic polymorph are similar, but the structures differ in the details of their crystal packing. In the triclinic system, the diaminopyrimidinone molecules are connected to one another via N-H...O and N-H...N hydrogen bonding to form infinite chains in the [011] direction. The chains are further hydrogen bonded to the water molecules, resulting in a three-dimensional network. In the monoclinic system, the diaminopyrimidinone molecules are hydrogen bonded together into two-dimensional networks parallel to the bc plane. The water molecules link the planes to form a three-dimensional polymeric structure.